Mucinous cystadenoma of a horseshoe kidney: A case report and literature review - Mitome, Taku; Yao, Masahiro; Naoko, Udaka; Fusayasu, Shusei; Izumi, Koji; Osaka, Kimito; Hayashi, Narihiko; Nakaigawa, Noboru; Nagashima, Yoji; Kubota, Yoshinobu (Canadian Urological Association Journal, 2015)
A 45-year-old man complained of a palpable mass in his left abdomen. Computed tomography showed a horseshoe kidney with a Bosniak type II complicated cyst from a left segment. Three years after his initial examination, due to the growing cystic lesion and the compression imposed on the urinary collecting system and surrounding organs, we performed a left heminephrectomy. The diagnosis was mucinous cystadenoma of the kidney. No recurrence was observed 6 months after surgery. The histopathology was unique since the inner surface of the cyst was covered by a mucin-positive columnar epithelium connected to a urothelium, with continuous transition between the two. This suggests that the mucinous tumour may have originated from a sequestered segment of the renal pelvic epithelium in the renal parenchyma.